2015
DOI: 10.1007/s10974-015-9438-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in skeletal muscle injury and regeneration: focus on antioxidant enzymes

Abstract: Reactive oxygen species (ROS) are generated in skeletal muscle both during the rest and contractile activity. Myogenic cells are equipped with antioxidant enzymes, like superoxide dismutase, catalase, glutathione peroxidase, γ-glutamylcysteine synthetase and heme oxygenase-1. These enzymes not only neutralise excessive ROS, but also affect myogenic regeneration at several stages: influence post-injury inflammatory reaction, enhance viability and proliferation of muscle satellite cells and myoblasts and affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(217 citation statements)
references
References 192 publications
(334 reference statements)
8
197
1
11
Order By: Relevance
“…Passive mechanical stretch of a muscle cell may generate ROS, which are required for proliferation and differentiation of muscle cells [Palomero et al, 2012]. Under physiological conditions, these ROS are balanced by ROS scavengers so that appropriate levels of ROS are maintained to facilitate cell proliferation [Bigarella et al, 2014;Kozakowska et al, 2015]. However, as stretching intensifies, more ROS are produced and they eventually outpace ROS scavenging, damaging many cellular components and causing adverse effects on cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive mechanical stretch of a muscle cell may generate ROS, which are required for proliferation and differentiation of muscle cells [Palomero et al, 2012]. Under physiological conditions, these ROS are balanced by ROS scavengers so that appropriate levels of ROS are maintained to facilitate cell proliferation [Bigarella et al, 2014;Kozakowska et al, 2015]. However, as stretching intensifies, more ROS are produced and they eventually outpace ROS scavenging, damaging many cellular components and causing adverse effects on cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, as stretching intensifies, more ROS are produced and they eventually outpace ROS scavenging, damaging many cellular components and causing adverse effects on cells. Indeed, elevated cellular levels of ROS are associated with apoptosis [Cheng et al, 1995;Pimentel et al, 2001;Kozakowska, et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The increase of oxidative stress in muscular dystrophy, which was acknowledged a long time ago (132,228), has been shown to correlate with the severity of the pathology (274) and is considered to contribute to the pathology of several muscular dystrophies (173). Interestingly, mutations in the antioxidant sepn1 gene cause SEPN1-related myopathy, a different class of muscle disease (14).…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…GRX2 is expressed in the mitochondria,165 GRX3 in the cytosolic and nuclear compartment, and monothiol GRX5 has a mitochondrial translocation signal and shares the active site motif of GRX3 166. Evidence has also shown that the GRX system can also catalyse reversible protein glutathionylation,167 which is an important redox regulatory mechanism, and control the redox state of thiol groups168 in situations where the redox environment is being compromised.…”
Section: Regulatory Reactive Oxygen and Nitrogen Species Enzymes Exprmentioning
confidence: 99%